Mean and True Positions of Planets as Described in Gaṇitagannaḍi: A Karaṇa Text on Siddhāntic Astronomy in Kannaḍa - Shylaja, B. S.; Javagal, Seetharam (History of Science in South Asia)

(untitled) (University of Alberta Library, 2021)
The unpublished seventeenth-century Kannaḍa-language mathematical work Gaṇitagannaḍi is transmitted in a single palm-leaf manuscript. It was composed by Śaṅkaranārāyaṇa Jōisaru of Śṛṅgeri and is a karaṇa text cast as a commentary on the Vārṣikatantrasaṅgraha by Viddaṇācārya. Gaṇitagannaḍi's unique procedures for calculations wer introduced in an earlier paper in volume 8 (2020) of this journal. In the present paper the procedures for calculations of the mean and true positions of planets are described.